Methods for the improvement of wrestlers' motor skill stability - Shiyan, V. V. (International Journal of Wrestling Science, 2013)
The purpose of the paper was to study the features of the wrestler`s motor skills (using the example of the flying mare-shoulder throw) along with progressive physical fatigue after specific loading. The experimental research devoted to the studies of stability of motor skill along with specially modeled physical fatigue were made with laboratory experiments on the members of the national Russian Greco-Roman wrestling youth team. Three stages were revealed and described in the dynamics of time indices of single throw phases, associated with the application of the motor skill within progressive physical fatigue (warming-up, stabilization and fatigue phases). The results experimentally substantiated the technique of pre-season improvement of elite wrestlers` individual technical mastership.